2016
DOI: 10.1080/10580530.2016.1188573
|View full text |Cite
|
Sign up to set email alerts
|

Citizens’ Adoption Behavior of Mobile Government (mGov): A Cross-Cultural Study

Abstract: Dr. Archer is a Special Advisor to the McMaster eBusiness Research Centre (MeRC), and a coordinator of the MSc eHealth program. His main research interests are in information security and privacy, eGovernment, and the adoption and use of electronic health records, personal health records, and chronic disease self-management by patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 76 publications
2
46
0
Order By: Relevance
“…Therefore, it quite clearly indicates that e-government research in SAARC countries is slowly moving from informational to transactional stage. As far as methodologies are concerned, survey (33) was found as the most commonly used methodology (e.g. [18]).…”
Section: Research Methods Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it quite clearly indicates that e-government research in SAARC countries is slowly moving from informational to transactional stage. As far as methodologies are concerned, survey (33) was found as the most commonly used methodology (e.g. [18]).…”
Section: Research Methods Analysismentioning
confidence: 99%
“…[27]) have been used five times each. However, the theories/models such as TRA [32], TPB [33], SCT [3], trustworthiness model [34], transaction cost theory [31] and perceived characteristics of innovating [8] have been used only once. The findings clearly indicate that the studies of e-government adoption are largely dependent on information systems/technology (IS/IT) adoption models.…”
Section: Theories/models Usedmentioning
confidence: 99%
“…Research carried out in a number of different areas such as Malaysia and rural China [12], [17], [18] have made use of adaptations of the Technology Acceptance Model (TAM) and provided examples of how a number of social, cultural and technical factors can usefully be included in the TAM to provide insights into the influences on citizens' intention to utilize m-government systems to access services and information. Cultural and technological factors like culture, trust and lack of necessary infrastructure have been demonstrated to be significant by comparative studies of mgovernment adoption in developing and developed countries [19], [20].…”
Section: Background and Contextmentioning
confidence: 99%
“…The adoption of m-government in Arab countries, however, still requires further research. Studies conducted in these areas [21], [22], [23], [20], [24] have revealed that factors such as trust, citizens' perceptions of the compatibility of mgovernment with their lifestyles, culture, awareness and the quality of the system are significant. Further, these studies show that there have been no empirical studies of mgovernment adoption in Saudi Arabia that includes factors like compatibility or culture.…”
Section: Background and Contextmentioning
confidence: 99%
“…Privacy and security relate to the safety of information (Shareef et al 2016b;Teo, Srivastava, and Jiang 2008). Transactional services require citizens to disclose personal information before a transaction can be completed (Beldad et al 2012); thus, 'privacy and security are reoccurring issues in e-commerce and e-government research' (Carter and Belanger 2005, p.9).…”
Section: Trustworthiness Of E-government and Associated Variablesmentioning
confidence: 99%